(untitled) - Donnelly, Denis (Reading, Mass, 1992)
Designed as a supplement to any introductory physics text, MathCAD(R)for Introductory Physics shows students how to model physics problems on the computer using the powerful Mathcad(R) software program. The power of the computer allows introductory physics students to solve complicated real-world problems that previously required upper level mathematics to solve. Each begins with a discussion of physical principles and numerical techniques. Then, tutorials, problems, and exploration exercises help readers model physical situations and analyze results. This text is available as an affordably priced package that contains The Student Edition of Mathcad(R), Release 2.5.
Keywords: Physics,Vật lý; Data processing,Xử lý dữ liệu